Gender Differences in Vocational High School Students’ Perceptions of Mobile-Assisted Language Learning for English Learning: A TAM-Based Study in Indonesia - Aura Khalisha Kamiliya; Ratih Novita Sari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates whether significant gender differences exist in vocational high school students’ perceptions of Mobile-Assisted Language Learning (MALL) for English learning based on the Technology Acceptance Model (TAM). Vocational students represent a distinctive EFL population whose preparation for direct workforce entry makes mobile English learning tools particularly relevant to their immediate educational goals, yet this group remains underrepresented in existing MALL research. A quantitative comparative survey design was employed involving 156 students from a vocational high school in South Jakarta, comprising 121 female and 35 male students, an imbalance reflecting the actual enrollment distribution of the participating study programs. Data were collected using an adapted fourteen-item TAM-based questionnaire measuring four constructs: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Use (ATU), and Behavioral Intention (BI), and were analyzed using a Mann-Whitney U test. The results revealed no statistically significant differences between male and female students across all four TAM constructs (all p > .10), with uniformly negligible small effect sizes, indicating that gender did not function as a statistically detectable differentiating factor in students’ perceptions of MALL within this sample. These findings suggest that vocational EFL practitioners may find it more productive to strengthen the overall quality of MALL integration through task design that connects mobile learning to students’ vocational English needs, rather than prioritizing gender-differentiated instructional approaches.